The Problems of English Speaking of Students at Yang Boo School, Keng Tung Town, Eastern Shan State of Myanmar - Ven. Arsing Na; Kanokkamalade , Veerakarrn; Khanetnog, Preecha (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
-